1970
DOI: 10.5424/sjar/2010084-1411
|View full text |Cite
|
Sign up to set email alerts
|

Changes in soil microbial biomass and activity in different Brazilian pastures

Abstract: Microbial biomass and activity are useful indices for assessing changes in soil ecosystems. The impact of different pastures on microbial biomass and activity was studied in a long-term experiment in Northeast Brazil. For our study the pastures were divided into plots: a) Brachiaria brizantha; b) Leucaena leucocephala; c) Cynodon dactilon; d) Panicum maximum. An adjacent area with native vegetation was used as reference. Soil samples were collected in 0-10 and 10-20 cm depths. No significant differences in soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 41 publications
6
17
0
3
Order By: Relevance
“…Lopes et al (2010) and Jakelaitis et al (2008) found similar results when comparing native forest with pasture, where the qCO 2 was significantly lower in the soil under native forest. The less stressful Table 2.…”
Section: Microbial Biomass and Metabolic Activitysupporting
confidence: 69%
“…Lopes et al (2010) and Jakelaitis et al (2008) found similar results when comparing native forest with pasture, where the qCO 2 was significantly lower in the soil under native forest. The less stressful Table 2.…”
Section: Microbial Biomass and Metabolic Activitysupporting
confidence: 69%
“…Os valores médios de C da biomassa microbiana (C microbiano) variaram de 37,3 a 92,8 mg C-CO 2 kg -1 (Figura 2a) e, embora esses sejam menores do que os normalmente registrados na literatura (Gatiboni et al, 2011;Kheyrodin et al, 2012;Balota et al, 2014), estão de acordo com os mencionados em estudos no Brasil (Lopes et al, 2010;Couto et al, 2013). Na análise do C microbiano para o solo coletado, não foram registradas diferenças significativas entre as áreas estudadas, dentro de cada época de coleta (agosto e novembro) (Figura 2a).…”
Section: Resultsunclassified
“…Nesses casos, de acordo com os autores, a aplicação de altos níveis de C lábil e a baixa relação C:N do dejeto estimularam a comunidade microbiana do solo. A respiração microbiana indica a atividade biológica e decomposição dos resíduos orgânicos do solo (Lopes et al, 2010), de modo que os resultados similares entre as áreas, ou a ausência de diferenças significativas, evidenciam que a atividade biológica do solo não foi influenciada pela adição de dejetos líquidos de suínos. Na segunda época de coleta, a maior respiração microbiana foi registrada para a área MN, sendo normal as áreas de vegetação nativa apresentarem respiração microbiana acima das demais (Lopes et al, 2010), e para a área A14, em relação à A2 (Figura 2b).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…This higher oxidative functional activity may be due to the higher carbon resources in the rhizosphere soil, which is considered as the driving force for microbial activity and density as reported by several workers (Bowen and Rovira, 1999;Yang et al, 2013). Lopes et al, (2010), where FDA hydrolysis activities were increased by native forest due to high deposition of residues. Other studies have also suggested that FDA activities are generally the most sensitive indicators of residue management changes on the belowground microbial community (Jordan et al, 1995).…”
Section: Effect Of Cr and P Fertilization On Fluroscence Diacetate Acmentioning
confidence: 97%